This action might not be possible to undo. Are you sure you want to continue?
Detailed derivation of the closed form solution for the Solow Model with a CobbDouglas
production function
Ugo Panizza
Notes for E028
These notes are based on Jones (2000) but provide more details on the derivation of the solution
and give an example of how to solve a simple differential equation.
1
Let us start by defining output with a CobbDouglas (CD) production function with CRS
α α −
=
1
t t t
L K Y
Population (and number of workers) is defined by
nt
t
e L L
0
= , where n is the rate of population
growth. Capital accumulation is given by:
t t t
dK sY K − =
&
Where s is the constant saving rate and d is the depreciation rate. We can write the above
equations in terms of output and capital per worker:
α
t t
k y =
t t t
k d n sk k ) ( + − =
α
&
(1)
The cool thing about the CD production function with CRS is that it yields the above differential
equation. This is called a Bernoulli equation and has a closed form solution (this is not the case
for other production functions). To solve the model, let us start by defining:
α −
=
1
t t
k z
note that:
t
t
t
t
t
y
k
k
k
z = =
α
and that:
) 1 ( α
α
− =
−
t t t
k k z
&
& .
Thus:
α
α
t
t
t
k
z
k
−
=
1
&
&
(2)
1
http://elsa.berkeley.edu/~chad/closedform.pdf. Jones also provides a short history of this solution. In these
notes I use the model with no technological progress. So, the solution is slightly different from the one
provided by Jones. The solutions become identical if A(0)=1 and g=0.
2
substituting (2) into (1), we get:
t t t
t
k d n sk k
z
) (
1
+ − =
−
α α
α
&
,
Or:
α
α α
−
+ − − − =
1
) )( 1 ( ) 1 (
t t
k d n s z& Î
t t
z d n s z ) )( 1 ( ) 1 ( + − − − = α α &
Define: ) )( 1 ( d n + − = α λ , and rewrite:
t t
z s z λ α − − = ) 1 ( &
Or: ) 1 ( α λ − = + s z z
t t
& (3)
Note that z describe the evolution of the capital to output ratio. So, the evolution of the capital to
output ratio is described by the above differential equation which is a linear differential equation
with constant coefficients. This type of equation has an easy solution (if you don’t remember the
solution, go and check out the appendix of these notes). In fact Eq. 3 resembles the equation in
(a1) with constant forcing function: ) 1 ( ) ( α − = s t g .
So, the solution to this DE must be similar to (a6). In fact, it is:
t
t
a
t
e
s
z
s
z k
λ
λ
α
λ
α
− −

.

\
 −
− +
−
= =
) 1 ( ) 1 (
0
1
Solving for k
t
, yields:
( )
α
λ
α
λ
α
λ
α
−
−
−
(
¸
(
¸

.

\
 −
− +
−
= =
1
1
0
1
1
) 1 ( ) 1 (
t
t t
e
s
z
s
z k
Rearranging, we get:
( )
α
λ
λ
α
−
−
(
¸
(
¸
−
−
+ =
1
1
0
1
) 1 (
t
t
e
s
z k
( )
α
λ λ α
λ
α
−
− − −
(
¸
(
¸
−
−
+ =
1
1
1
0
1
) 1 (
t t
t
e
s
e k k
( )
α
α α α
−
+ − − + − − −
(
¸
(
¸
−
+
+ =
1
1
) )( 1 ( ) )( 1 ( 1
0
1
t d n t d n
t
e
d n
s
e k k (4)
3
Note that k
0
is the initial level of capital and
α −

.

\

+
1
1
d n
s
is the steady state value of the capital
stock.
So, at any point in time, the capital stock is a weighted average of these two values and
the weights are an exponential function of time. When t goes to infinity, the capital stock
converges to its steady state value (because exp(1α)(n+d)t goes to zero). Note that
) )( 1 ( d n + − = α λ measures the speed of convergence.
Of course, we can write (4) in terms of output per worker:
( )
α
α
α α α α
−
+ − − + − − −
(
¸
(
¸
−
+
+ =
1
) )( 1 ( ) )( 1 ( ) 1 (
0
1
t d n t d n
t
e
d n
s
e y y (5)
4
Appendix: Intuition on how to solve a simple linear DE with constant coefficients.
Assume you have a differential equation that takes the following form:
) (
1 0
t g y a y a
t t
= + & (a1)
t t
y a y a
1 0
+ & is called the homogeneous part of the DE, ) (t g is called the forcing function.
If ) (t g =0, the DE is called homogeneous, if not the equation is called nonhomogenous.
When ) (t g is constant (i.e., it does not depend on t), it is very easy to transform a non
homogenous DE into a homogenous DE.
Let’s start by focusing on the homogenous part and define
0
1
a
a
a = . Let us also assume
that the forcing function is constant and γ = ) (t g . We can then rewrite Equation (a1) as:
γ = +
t t
ay y& Î 0 =

.

\

− +
a
y a y
t t
γ
& .
Let us now define

.

\

− =
a
y x
t t
γ
. Since
a
γ
is a constant,
t t
y x & & = . Thus,
t t t t
ax x
a
y a y + =

.

\

− + & &
γ
=0 Î
t t
ax x − = & (a2)
and we have transformed our nonhomogenous function into a homogenous function.
Now, let’s try to guess a solution for this function.
Note that
t t
ax x − = & looks like the derivative of an exponential function (if
h
e v = , then
h
e h
dh
dv
) 1 ( − = ). So, let’s try with an exponential function. And guess that:
t
t
Ae x
δ
= ,
where A and δ are the parameters we need to find in order to solve our DE.
If
t
t
Ae x
δ
= , then:
t
t
t
x Ae x δ δ
δ
= = &
Substitute this into our DE in (a2):
0 = + = +
t t
t t
aAe Ae ax x
δ δ
δ & ,
5
this can be rewritten as:
( ) 0 = + a Ae
t
δ
δ
(a3)
One solution for this equation is clearly:
( ) a − = δ
So, we can start by modifying our first guess and write it as:
at t
t
Ae Ae x
−
= =
δ
(a4)
This is called the GENERAL Solution of the DE
We can now specify a boundary condition by identifying the value of x at some point in
time (time zero is usually a good choice). Let us set the value of x at time zero to be
0
x . Then:
A Ae x = =
0
0
δ
Substituting into (a4), we get:
at
t
e x x
−
=
0
(a5)
This is the UNIQUE solution to our DE.
Let’s remember that our equation was not homogenous.
0 =

.

\

− +
a
y a y
t t
γ
&
No big deal.
Since

.

\

− =
a
y x
t t
γ
, then

.

\

− =
a
y x
γ
0 0
, and
at
t
e
a
y x
−

.

\

− =
γ
0
,
and, finally
at
t
e
a
y
a
y
−

.

\

− + =
γ γ
0
(a6)
we get: & zt α kt = sktα − (n + d )kt . In fact Eq. This type of equation has an easy solution (if you don’t remember the solution. the solution to this DE must be similar to (a6).substituting (2) into (1). 1−α Or: & zt = s(1 − α ) − (1 − α )(n + d )kt1−α & zt = s(1 − α ) − (1 − α )(n + d ) zt Define: λ = (1 − α )(n + d ) . So. go and check out the appendix of these notes). the evolution of the capital to output ratio is described by the above differential equation which is a linear differential equation with constant coefficients. and rewrite: & zt = s (1 − α ) − λzt & Or: zt + λzt = s (1 − α ) (3) Note that z describe the evolution of the capital to output ratio. So. 3 resembles the equation in (a1) with constant forcing function: g (t ) = s(1 − α ) . In fact. we get: (1 − α ) s 1−α kt = z0 + 1 − e − λt λ ( ) 1 (1 − α ) s 1 1−α kt = k 0 −α e − λt + 1 − e − λt λ ( ) 1 s 1 1− α kt = k0 −α e − (1−α )( n + d )t + 1 − e − (1−α )( n + d ) t n+d ( ) 1 (4) 2 . yields: kt = zt ( ) 1 1− α (1 − α ) s (1 − α ) s − λt 1−α = + z0 − e λ λ 1 Rearranging. it is: kt 1− a = zt = (1 − α ) s λ (1 − α ) s − λt + z0 − e λ Solving for kt.
Note that λ = (1 − α )(n + d ) measures the speed of convergence. the capital stock converges to its steady state value (because exp(1α)(n+d)t goes to zero). Of course. we can write (4) in terms of output per worker: 1 s ( 1− α yt = y01−α )α e − (1−α )( n + d ) t + 1 − e − (1−α )( n + d ) t n+d ( ) α (5) 3 . at any point in time. So. s 1− α Note that k0 is the initial level of capital and is the steady state value of the capital n+d stock. When t goes to infinity. the capital stock is a weighted average of these two values and the weights are an exponential function of time.
xt = yt . the DE is called homogeneous.. g (t ) is called the forcing function. then: & xt = δAeδt = δxt Substitute this into our DE in (a2): & xt + axt = δAeδt + aAeδt = 0 . So. then dv = (h − 1)e h ). let’s try with an exponential function. Now. let’s try to guess a solution for this function. Since is a constant. it does not depend on t). When g (t ) is constant (i. if not the equation is called nonhomogenous. a Let us now define xt = yt − γ & & . & Note that xt = −axt looks like the derivative of an exponential function (if v = e h . a a & xt = −axt (a2) γ γ & & yt + a yt − = xt + axt =0 a and we have transformed our nonhomogenous function into a homogenous function.e. Thus.Appendix: Intuition on how to solve a simple linear DE with constant coefficients. Let’s start by focusing on the homogenous part and define a = a1 . If xt = Aeδt . where A and δ are the parameters we need to find in order to solve our DE. 4 . And guess that: dh xt = Aeδt . Let us also assume a0 that the forcing function is constant and g (t ) = γ . Assume you have a differential equation that takes the following form: & a0 yt + a1 yt = g (t ) (a1) & a0 yt + a1 yt is called the homogeneous part of the DE. If g (t ) =0. it is very easy to transform a nonhomogenous DE into a homogenous DE. We can then rewrite Equation (a1) as: & yt + ayt = γ γ & yt + a yt − = 0 .
we get: xt = x0e − at This is the UNIQUE solution to our DE. Let us set the value of x at time zero to be x0 . Since xt = yt − γ γ . then x0 = y0 − . and a a γ xt = y0 − e − at . Let’s remember that our equation was not homogenous. (a5) γ & yt + a yt − = 0 a No big deal. Then: x0 = Aeδ 0 = A Substituting into (a4).this can be rewritten as: Aeδt (δ + a ) = 0 One solution for this equation is clearly: (a3) (δ = −a ) So. we can start by modifying our first guess and write it as: xt = Aeδt = Ae− at (a4) This is called the GENERAL Solution of the DE We can now specify a boundary condition by identifying the value of x at some point in time (time zero is usually a good choice). a and. finally yt = γ γ + y0 − e − at a a (a6) 5 .
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue listening from where you left off, or restart the preview.